EFFECT OF THIRD PARTY FUNDS GROWTH, CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO AND RETURN ON ASSETS ON CREDIT IN GROWTH RURAL BANKS IN DENPASAR - Ni Wayan Sulistiyani; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (AIBPM Publisher, 2019)
This study aims to examine the factors that influence bank lending such as Third Party Funds, Capital Adequacy Ratio, Non Performing Loans, Loan To Deposit Ratio, and Return On Assets towards bank lending. The population of this study is Rural Banks in Denpasar City for the period 2016-2017. In this study the method of determining the sample used is saturated sample. The analysis technique used is multiple linear regression, and hypothesis testing using the -t test to test the partial regression coefficient, and the -f test to test the effect together with the level of 5% . Besides that, a classic assumption test was also conducted which included normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results showed Third Party Funds and Loan To Deposit Ratio, have a positive and significant effect on bank lending. Third, Capital Adequacy Ratio, Non Performing Loans and and Return On Assets have a negative and significant effect on bank lending.